Long‐term trends and outcomes of anterior vitrectomy in Western Australia. (5th June 2014) - Clark, Antony; Morlet, Nigel; Ng, Jonathon Q.; Preen, David B.; Semmens, James B.
Abstract Purpose To describe trends, risk factors and outcomes of anterior vitrectomy during cataract and intraocular lens (IOL) surgery. Methods All patients 16 years and older undergoing cataract and IOL surgery in Western Australia (WA) from January 1980 to December 2001 (n = 115 815) were included. Hospital administrative data were used to identify all cataract and IOL procedures and subsequent admissions for retinal detachment, IOL dislocation, endophthalmitis and pseudophakic corneal oedema. Data were validated with chart review and analysed to identify trends and risk factors for anterior vitrectomy and the risk of subsequent complications. Results In total, 1390 (1.2%) anterior vitrectomies were performed. The rate increased with change in surgical technique. Significant risk factors for anterior vitrectomy were age <50 years (OR 1.31), male sex (OR 1.23), IOL procedure (OR 11.45) and operations in public hospitals (OR 1.99) or rural/remote (OR 1.40) areas. Anterior vitrectomy was strongly associated with increased risk of retinal detachment (RD) (RR 18.5), endophthalmitis (RR 3.6), IOL dislocation (RR 21.1) and pseudophakic corneal oedema (RR 17.3). Retinal detachments and IOL dislocations occur earlier after anterior vitrectomy. Conclusion Anterior vitrectomy rates have remained stable since the introduction of phacoemulsification. Anterior vitrectomy is a major risk factor for serious complications compared with uncomplicated surgery, particularly RD and IOL dislocation. We identified an increasing trend in anterior vitrectomy being performed during extracapsular and IOL surgery.